Genotypic differences in seed yield, K : Na ratio and leaf metabolism of cumin (Cuminum cyminum L.) under salt stress - Kathju, B K Garg, U Burman, S (Journal of Spices and Aromatic Crops, 2003)
Responses of five genotypes (UC-198, UC-220, UC-223, RZ-19 and RZ-209) of cumin (Cuminum cyminum L.) irrigated with water having two levels of salinity (0.2 and 10 dSm-1) on shoot dry weight, seed yield, K : Na ratio and leaf metabolism at the flowering stage were studied. Increased salinity significantly reduced seed yield and shoot dry matter in all the genotypes. However, RZ-19 displayed higher salt tolerance than UC-198 and RZ-209 whereas UC-220 and UC-223 showed intermediate tolerance to salinity in terms of seed weight and shoot dry matter. Adverse effects of salinity on the levels of total chlorophyll, soluble protein, free amino acids, starch, reducing sugars and nitrate reductase activity were consistently less in tolerant genotype RZ-19 as compared to sensitive genotypes, UC-198 and RZ-209. Moreover sensitive genotypes had higher concentration of Na and lower concentration of K and consequently lower K : Na ratio under salt stress as compared to the tolerant genotype. These differential genotypic responses have been discussed in the light of the present knowledge.